Peace Building by Cultural Communities: Learning from Indonesian Cultures and Several Considerations - Immanuel, Jimmy Marcos (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2010)
In human life, culture is really important. Culture serves many functions, often overwhelming many things in life. It shapes the way we live, think, speak, act, relate to each other, and so on. Even within the framework of violence and peace, every culture projects ambiguity in its functions. It can either be a source of violence or a source for peace building. Starting from this ambiguity, forms of violence and/or conflicts in many places (especially in Indonesia) can be reduced by culture through cultural communities, in a frame of peace building. Our efforts for peace building in this case need to include internal and external cultures, sources of power, and how to foster independence from the agent of culture from the ambiguity and other factors which cause violence. This article will explore the role of some of Indonesian local cultures in building peace. In addition, it will show that education, as a source of power, is the most important way to raise peopleâs consciousness to live in peace.